Modelling Subgrade Modulus Using Deflection of Falling Weight Deflectometer - Siegfried Siegfried; Sufanir A M S (International Conference on Engineering and Technology Development (ICETD), 2017)
The value of sub grade modulus is required for pavement management system (PMS), design and evaluation of a pavement system. In the overlay thickness design the first thing should be carried out is to predict the modulus of existing sub grade. While in the PMS this value is used for reference in segmenting of tested road links. There are several methods available to calculate subgrade modulus based on the Falling Weight Deflectometer (FWD) deflections. Generally, calculation of sub grade modulus from FWD deflections need information of total pavement thickness above sub grade level. This information is quite difficult because it needs testing using equipment called Ground Penetrating Radar (GPR). This equipment is relatively expensive and the main thing it needs the skilled engineers to interpret the GPR results. This research aims to find the correlation between FWD deflection to that of the modulus of existing subgrade, so that the calculation of sub grade modulus based on FWD deflection does not need the information of total pavement thickness anymore. The research starts by simulating pavement under standard traffic load (4200 kg) and then calculate the surface deflection on the points which are located as exactly same as the FWD geophone are. The simulated pavement model consists of 3 layers i.e. surface layer of flexible, base layer of granular, and sub grade. A computer program called KenPave is used for this simulation. This program is able tocalculate the deflection, stress, and strain in any location of pavement system by inputting layer thicknesses, modulus of each layer as well as Poisson’s ratio. There are 3800 variations of simulated pavement system which vary modulus and thickness of each layer.After that it is carried out modeling of subgrade modulus and the value of deflection at the 900 mm offset (D 900). It is then obtained a logarithmic model that correlates the value of sub grade modulus and the deflection at 900 mm offset. The correlation factor is quite good (r21, A M S Sufanir = 87.5%). The final step of the research is to test this model using field data of FWD and the results are compared to back calculation results using FWDArea and Elmod programs. It is then found that when the results are plotted each other, they all fall around line of equality. It means that the sub grade modulus obtained from the model is not significantly different to that of back calculation result. In the other words, the logarithmic model between sub grade modulus and FWD deflection of 900 mm offset is acceptable. This model could help pavement engineers for predicting the modulus of existing sub grade very fast.